Molecular docking and pharmacokinetic prediction of isoniazid and curcumin compounds against N-acetyltransferase 2 (NAT2) protein - Gayatri Simanullang; Annisa Maulidia Rahayyu; Novrilia Atika Nabila; Akmal Hammami; Intan Kusuma Wardani (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
NAT2 serves as the key enzyme responsible for metabolizing the INH compound, with its expression and functional activity significantly contributing to the risk of hepatotoxicity. Due to the possible inhibitory role of curcumin on NAT2, it is important to assess its effect on the metabolic processing of INH and to examine the enzyme-related interactions that may occur between drugs. Molecular docking studies demonstrated that curcumin can localize in the hydrophobic pocket and form a strong bond with NAT2. The aim of this study was to predict the potential interaction of the isoniazid and curcumin compounds against NAT2 protein. In this study, NAT2 protein (PDB ID: 2PFR) was used as a receptor. The results obtained showed the binding energies of native ligand, isoniazid, and curcumin were -5.78, -4.47, -8.35 kcal/mol, respectively. The findings of this research suggest that curcumin is capable of suppressing NAT2 activity, thereby affecting the pharmacokinetics of INH. These results may offer insights into minimizing INH-related liver toxicity and enhancing its effectiveness through co-administration with curcumin.